2004
DOI: 10.2105/ajph.94.2.300
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Tobacco Use Among Chinese Americans

Abstract: Acculturation was positively associated with never smoking among men but not with smoking cessation. However, knowledge of tobacco-related health risks was associated with both. Results indicate a need for language-specific educational interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 29 publications
8
85
2
Order By: Relevance
“…The current study, on the contrary, showed an inverse association between BMI and acculturation. This may be due to the way acculturation was defined: two categorical variables regarding English language and media use [13]. The use of English language and media may be an indicator of higher educational attainment and socio-economic status (SES), both of which have been associated with a lower body weight [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study, on the contrary, showed an inverse association between BMI and acculturation. This may be due to the way acculturation was defined: two categorical variables regarding English language and media use [13]. The use of English language and media may be an indicator of higher educational attainment and socio-economic status (SES), both of which have been associated with a lower body weight [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the data source and sample selection methods is reported elsewhere [13,14]. Briefly, eligible households were obtained from the Flushing and Sunset Park white pages, using a list of 867 unique Chinese surname spellings identified in consultation with Chinese linguists.…”
Section: Data Sources and Sample Selectionmentioning
confidence: 99%
“…Smoking among Chinese-American females has ranged from 2.6% [2] to 4% [17] and is 6% in the CHIS sample. Our analysis presented here is the first to describe demographic and social determinants of smoking in Chinese-American adult females and it is interesting that there is a trend that is opposite of that seen among Chinese-American males: Smoking rates tend to be higher among U.S.-born Chinese-American females than among those who are foreign-born.…”
Section: Chinese-american Smoking Datamentioning
confidence: 95%
“…Several surveillance efforts have been conducted in various Chinese-American communities in New York City [17], Chicago's Chinatown [3], Philadelphia's Chinatown [7], Pennsylvania and New Jersey [18,19], and San Francisco [2]. Smoking prevalence among Chinese-American men has ranged in these studies from 34% [3] to 16% [2].…”
Section: Chinese-american Smoking Datamentioning
confidence: 99%
“…Regional surveys conducted in Asian languages indicate that Chinese males are at high risk for excess tobacco-related morbidity and mortality; smoking prevalence rates in this population range from 28% to 36% (Ma, Shive, Tan, & Toubbeh, 2002;Shelley et al, 2004;Yu, Chen, Kim, & Abdulrahim, 2002). These rates are higher than those reported in the Behavioral Risk Factor Surveillance System, which presents aggregated data for Asian Americans and therefore may underestimate risk for specific AAPI subgroups, such as Chinese Americans (Centers for Disease Control and Prevention [CDC], 1992[CDC], , 2004U.S.…”
Section: Introductionmentioning
confidence: 99%